Lonicerae Japonicae Flos Extract Promotes Sleep in Sleep-Deprived and Lipopolysaccharide-Challenged Mice - Hua, Ruifang; Ding, Yan; Liu, Xiaolong; Niu, Bingxuan; Chen, Xinfeng; Zhang, Jingjing; Liu, Kerui; Yang, Pei; Zhu, Xiaofei; Xue, Jintao; Wang, Hui (Frontiers in Neuroscience, 2022)
Lonicerae Japonicae Flos (LJF) is commonly used in Chinese herbal medicines and exhibits anti-viral, anti-oxidative, and anti-inflammatory properties. The reciprocal relationship between sleep, the immune system and the central nervous system is well established. In this study, we used the mouse model to analyze the beneficial effects of the LJF extract on the sleep-wakefulness cycle under basal, sleep deprived and lipopolysaccharide (LPS)-induced inflammatory conditions and the potential underlying mechanisms. Polysomnography data showed that LJF increased the time spent in non-rapid eye movement (NREM) sleep during the day under basal conditions. LJF treatment reduced the latency to sleep and increased the time spent in rapid eye movement (REM) sleep during recovery from acute sleep deprivation. Furthermore, LJF-treated mice showed increased REM sleep and altered electroencephalogram (EEG) power spectrum in response to intra-peritoneal injection of LPS. LJF inhibited microglial activation and significantly reduced the levels of proinflammatory cytokines such as IL-6, TNF-α, and IL-1β in the blood serum, hippocampus, and medial prefrontal cortex (mPFC) tissues in the LPS-challenged mice. Moreover, LJF increased the time spent in REM sleep in the LPS-challenged mice compared to the control mice. These results suggested that LJF stimulated the sleep drive in response to acute sleep deprivation and LPS-induced inflammation, thereby increasing REM sleep for recovery and neuroprotection. In conclusion, our findings demonstrated the clinical potential of LJF in treating sleep disturbances associated with sleep deprivation and neuro-inflammation.